Dampak Aktivitas Penambangan Pasir Laut Terhadap Lingkungan di Desa Sathean Kabupaten Maluku Tenggara - Leisubun, Adriana Wulan Tari; Andaria, Kalvin Salindeho; Rifani, Irfan; Putri, Anindya Puspita (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
The purpose of this study was to evaluate the environmental impact of sea sand mining in Sathean village, Kei Kecil sub-district, Southeast Maluku district. This study focuses on the state of the environment around marine sand mining and the impacts of these activities. Qualitative research is the chosen research method. The results show that marine sand mining damages the biological quality of marine and coastal waters through increased abrasion. Economic income for miners and mining workers increases as a result of social conditions caused by sea sand mining, but decreases for fishing communities due to reduced fish catches and pearl cultivators because pearl growth is not optimal due to damage to the aquatic environment.